Management : - Bateman, Thomas S. (McGraw Hill, 2007)
Using a traditional, functional approach to management, stressing how managers use planning, organization, leadership and control, this text looks at the "new economy". Despite the rise in e-commerce and the trials of dot.com companies, management fundamentals remain the same. This book shows hoe four underlying themes - quality, cost, innovation and speed - drive competitive advantage in the new economy, whether applied to a traditional or dot.com company. The accompanying CD-ROM contains self-assessment exercises and flash technology, as well as PowerPoint